HFE C282Y homozygotes have reduced LDL cholesterol: the Atherosclerosis Risk in Communities (ARIC) Study - Pankow, James S. (2008)
Recent studies have raised questions about the long-term health risks for individuals with mutations in the HFE gene, although previous studies may have been plagued by selection bias or lack of population-based comparison groups. We examined cardiovascular disease risk factors, iron and liver biomarkers, and morbidity and mortality associated with the C282Y and H63D variants of HFE in the ARIC study, a population-based cohort of nearly 16,000 U.S. white and black men who were 45–64 years old at baseline. Subjects were followed for an average of 15 years for death, incident coronary heart disease, stroke, and heart failure, and 8 years for incident diabetes. The prevalence of C282Y homozygosity was 0.42% (45/10,800) in whites, similar to other North American population-based studies. C282Y homozygotes had statistically significantly lower mean LDL cholesterol and fibrinogen and higher mean levels of iron (ferritin, transferrin saturation) and liver biomarkers (alanine aminotransferase, Hepascore) compared to HFE wild-type subjects. Rates of all-cause mortality, cardiovascular disease, and diabetes were similar across HFE genotypes. These prospective, population-based data indicate higher serum iron indices and possible mild liver dysfunction or disease in some C282Y homozygotes, but provide little evidence that HFE C282Y or H63D mutations are related to all-cause mortality, cardiovascular disease, or diabetes. Reduced LDL in C282Y homozygotes may be due to effect of excess iron on cholesterol metabolism and lipoprotein formation in the liver.